2011
DOI: 10.1111/j.1399-6576.2011.02586.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the efficacy and safety of fibrinogen concentrate substitution in adults

Abstract: In conclusion, the results of the available controlled trials suggest that the administration of fibrinogen concentrate was effective and safe. However, because all studies identified were of inadequate quality, these findings need to be confirmed by randomised controlled trials of sufficient size and long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 21 publications
2
32
0
1
Order By: Relevance
“…Several studies and systematic reviews have suggested that fibrinogen concentrate therapy may be effective in controlling perioperative bleeding and in reducing transfusion requirements as well as blood loss in cardiovascular surgery [25-27]. The remarkable observation in our retrospective study is that administration of fibrinogen concentrate after the CPB termination sufficiently elevated the plasma fibrinogen concentration for hemostasis in TAA surgery, while only FFP transfusion did not (Figures  1, 2, 3 and 4).…”
Section: Discussionmentioning
confidence: 52%
“…Several studies and systematic reviews have suggested that fibrinogen concentrate therapy may be effective in controlling perioperative bleeding and in reducing transfusion requirements as well as blood loss in cardiovascular surgery [25-27]. The remarkable observation in our retrospective study is that administration of fibrinogen concentrate after the CPB termination sufficiently elevated the plasma fibrinogen concentration for hemostasis in TAA surgery, while only FFP transfusion did not (Figures  1, 2, 3 and 4).…”
Section: Discussionmentioning
confidence: 52%
“…The utility of fibrinogen concentrate has been observed in multiple surgical circumstances, including cardiac, obstetrical and traumatic surgeries, with successful decreased severity of bleeding (4). In addition to fibrinogen concentrate, our patient was supplemented with washed platelets and pRBCs, which has previously been reported during OLT after anaphylaxis to plasma containing blood products (5).…”
Section: Discussionmentioning
confidence: 99%
“…Existen, también, 2 revisiones sistemáticas y otra de la Cochrane que concluyen que el tratamiento con Fb disminuye las necesidades transfusionales y el sangrado postoperatorio 159,182,183 . No obstante, en pacientes quirúrgi-cos se ha observado que los incrementos del Fb plasmático son de corta duración, y a las 24 h de la cirugía los niveles de Fb son similares a los de los pacientes que no lo recibieron 165,180,184 .…”
Section: Fibrinógenounclassified